Treating diabetes during pregnancy. (February 2015) - Klein, Jamie; Charach, Ron; Sheiner, Eyal
<x xml:space="preserve">Abstract</x> Introduction: Gestational diabetes mellitus (GDM), defined as glucose intolerance with first recognition or onset during pregnancy, is steadily rising in prevalence. GDM affects ∼ 3 – 5% of pregnancies in the US and is associated with significant adverse perinatal and maternal outcomes. Diagnosing and treating GDM early in pregnancy is of utmost importance as it can prevent poor outcomes such as macrosomia, shoulder dystocia and obstetric complications. Areas covered: This review describes the importance of treating GDM and the various available interventions for glycemic control in women with GDM, including the latest evidence regarding pharmacological treatments and specifically anti-hyperglycemic agents. It deals with timing of pharmacological treatments, recommended doses and what pharmacological agent should be used. Expert opinion: Unless diagnosed late during pregnancy, a stepwise approach is the best way to treat GDM, beginning with diet and exercise and proceeding to pharmacological interventions if failure occurred. Although insulin is the dominant treatment, the use of anti-hyperglycemic agents such as glyburide and metformin in treating GDM has gained popularity and consideration should be made using these agents as first-line pharmacological treatment. Anti-hyperglycemic agents do not require frequent monitoring or injections and may therefore appeal more to patients. Further studies are needed regarding long-acting insulin and other anti-hyperglycemic agents such as thiazolidinediones, as well as identifying treatment options more specific to an individual based on risk factors and other variables predicting treatment outcomes in GDM.